Effect of temperature on performance of finishing swine - David A Nichols; D R Ames; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1980)
We used 128 barrows averaging approximately 160 lbs. and temperatures of 32, 41, 50, 59, 68, 77, 86 and 95 F to study the effects of temperature on growth and efficiency. No significant differences in performance were observed for pigs housed at temperatures from 50 to 77 F. Those housed at 32 and 41 F were significantly less efficient than those housed at any other temperature. Pigs exposed to 95 F ate significantly less and had lower daily gains than any other group. With increased energy costs, temperature for maximum performance may no longer be the temperature for most economical performance. Results from these studies indicate that environmental modifications for heating or cooling may not be justified when temperatures range from 50 to 77 F.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Temperature; Performane; Finishing pigs